THE СANONS OF SPIRITUALITYINLINAKOSTENKO’S HISTORIC PHILOSOPHICAL DRAMATIC POEM “SCYTHIAN ODYSSEY” - Войтенко, Г. М. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
Sharpmoments discloses the philosophical psychology of heroes of the poem “Scythian Odyssey”.